How medical students in their pre-clinical years perceive psychiatry as a career : the study from Belgrade - Marić-Bojović, Nađa (Array, 2009)
Taking the Initiative to evaluate students’ affinity toward psychiatry seems to be a global issue and is an essential part of programs to improve the status of the profession. The aim of this study is to explore medical students’ attitudes toward psychiatry in comparison to other residencies (internal medicine, surgery, pediatrics, gynecology and general medicine) in the pre-clinical year and to observe which factors influence the creation of these attitudes. Fifteen percent of students stated that psychiatry was their career of choice, while 25% expressed a strong aversion. Psychiatry was ranked less attractive than internal medicine, surgery and pediatrics, but more attractive than general medicine or gynecology. Those who like psychiatry attributed more importance to an interesting and challenging job than to prestige and financial reward